The effects of physical exercises on c-reactive protein in patients with post ischemic stroke - Laswati, Hening; Andriana, Meisy; Subadi, Imam; Yuanita, Ida (Folia Medica Indonesiana, 2017)
Several studies have recently highlighted the important role of physical exercise in regulation inflammatory status, but there is relatively little known about markers of inflammation levels after physical exercise in post ischemic stroke patients. The aims of this study to provide the effects of physical exercise using Partial Body-Weight Supported Treadmill Training –Audio Cues (PBWSTT-AC) and Traditional method on the level of inflammatory markers C-Reactive Protein (CRP). This study using pretest-postest control group design, 14 post ischemic stroke patients were randomized and allocate to two groups: Group1 (control group) received traditional walking exercise and group 2 received PBWSTT-AC. The walking exercise study were conducted for 20 minute 3 times a week for 12 sessions (4 weeks). Before and after 12 session of exercises, the serum levels of CRP were determined using immunoserology. All statistical test were carried out using SPSS 17 and statistical significance was set at p<0.05 for all analysis. The CRP levels between group were compared using Student t test or Mann-Whitney test. From multiple comparisons statistic result, no significant difference between groups (p=0.898), that seem in this study the levels of CRP of poststroke patients is not influenced by the Traditional training and PBWSTT-AC. The conclusion of this study that both traditional method and PBWTT-AC in 4 weeks exercise training seem have no effect on CRP levels.